Urbain forests of the wilaya of Constantine, towards enhancing their role as a space of leisure - Benfoughal, Meriem; Boukerzaza, Haceni (Journal of Human Sciences, 2021)
In recent years, urban forests have seen an increase in their use by citizens. At the moment when real data on the volume of visitors, their needs or the supervision of their activities, remains completely absent. Although the wilaya of Constantine has benefited from a program for the development of recreational forests, these have not yet been carried out. For this and given the lack of scientific studies in this context, we have tried, through this article, to diagnose the state of affairs and to present the necessary data which can be a basis for further research based on the collection of theoretical data as well as field research. This work is essentially based on the selection of three forests as a case study, also analyzing the new projects following the SWOT method. From our research we have been able to define the fundamental basic elements which help to develop and boost the activity of recreation in forests in an equivalent way.